Modified Projective Synchronization of Chaotic Systems with Noise Disturbance, an Active Nonlinear Control Method - Hamed Tirandaz; Mohsen Ahmadnia; Hamid Reza Tavakoli (International Journal of Electrical and Computer Engineering (IJECE), 2017)
The synchronization problem of chaotic systems using active modified projective nonlinear control method is rarely addressed. Thus the concentration of this study is to derive a modified projective controller to synchronize the two chaotic systems. Since, the parameter of the master and follower systems are considered known, so active methods are employed instead of adaptive methods. The validity of the proposed controller is studied by means of the Lyapunov stability theorem. Furthermore, some numerical simulations are shown to verify the validity of the theoretical discussions. The results demonstrate the effectiveness of the proposed method in both speed and accuracy points of views.